Genetic Variation of G6PD and CYP2D6: Clinical Implications on the Use of Primaquine for Elimination of Plasmodium vivax - Stewart, Alexandra G. A.; Zimmerman, Peter A.; McCarthy, James S. (Frontiers in Pharmacology, 2021)
Primaquine, an 8-aminoquinoline, is the only medication approved by the World Health Organization to treat the hypnozoite stage of Plasmodium vivax and P. ovale malaria. Relapse, triggered by activation of dormant hypnozoites in the liver, can occur weeks to years after primary infection, and provides the predominant source of transmission in endemic settings. Hence, primaquine is essential for individual treatment and P. vivax elimination efforts. However, primaquine use is limited by the risk of life-threatening acute hemolytic anemia in glucose-6-phosphate dehydrogenase (G6PD) deficient individuals. More recently, studies have demonstrated decreased efficacy of primaquine due to cytochrome P450 2D6 (CYP2D6) polymorphisms conferring an impaired metabolizer phenotype. Failure of standard primaquine therapy has occurred in individuals with decreased or absent CYP2D6 activity. Both G6PD and CYP2D6 are highly polymorphic genes, with considerable geographic and interethnic variability, adding complexity to primaquine use. Innovative strategies are required to overcome the dual challenge of G6PD deficiency and impaired primaquine metabolism. Further understanding of the pharmacogenetics of primaquine is key to utilizing its full potential. Accurate CYP2D6 genotype-phenotype translation may optimize primaquine dosing strategies for impaired metabolizers and expand its use in a safe, efficacious manner. At an individual level the current challenges with G6PD diagnostics and CYP2D6 testing limit clinical implementation of pharmacogenetics. However, further characterisation of the overlap and spectrum of G6PD and CYP2D6 activity may optimize primaquine use at a population level and facilitate region-specific dosing strategies for mass drug administration. This precision public health approach merits further investigation for P. vivax elimination.